2022
DOI: 10.3390/ani12111347
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Characterization of Klebsiella pneumoniae Isolates from Wild Animals in Central Italy

Abstract: Despite Klebsiella pneumoniae being widely recognized as a nosocomial pathogen, there is a critical lack in defining its reservoirs and sources of infections. Most studies on risk factors have focused on multidrug-resistant (MDR) isolates and clinically-oriented questions. Over a two-year period, we sampled 131 wild animals including mammal and bird species from three regions of Central Italy. All typical colonies isolated from the analytical portions were confirmed by real-time PCR and identified by MALDI-TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Chiaverini A et al isolated 16 K . pneumoniae strains from wild animals (15 mammals and one bird), of which 56.2% (9/16) were classified as MDRs, with rates of resistance to tetracycline, trimethoprim and β-lactams of 18.8%–100.0% [ 39 ]. The reason for the low isolation rates of MDR strains in this study may be because captive giant pandas do not live in groups so bacterial spread between individuals is low, or it may be because of their better habitat.…”
Section: Discussionmentioning
confidence: 99%
“…Chiaverini A et al isolated 16 K . pneumoniae strains from wild animals (15 mammals and one bird), of which 56.2% (9/16) were classified as MDRs, with rates of resistance to tetracycline, trimethoprim and β-lactams of 18.8%–100.0% [ 39 ]. The reason for the low isolation rates of MDR strains in this study may be because captive giant pandas do not live in groups so bacterial spread between individuals is low, or it may be because of their better habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence we recorded was in line with the findings of other authors. In particular, Chiaverini et al [ 44 ] in a very recent study conducted in central Italy isolated from Pica Pica a strain of K. pneumoniae , which showed resistance to several antimicrobials. Similarly, Foti et al in 2017 [ 18 ] reported two strains of K. pneumoniae , isolated from cloacal samples of migratory birds in Italy, and exhibiting resistance to 14 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Kp isolates from wild animals were collected in the framework of regional plans of epidemiological surveillance and monitoring of diseases in wild fauna, in the frame of the national plan of surveillance of West Nile disease and Usutu for bird species ( Chiaverini et al, 2022 ). In food, food-producing environments, and feed, Kp isolates were detected during monitoring plans for foodborne pathogens.…”
Section: Methodsmentioning
confidence: 99%
“…Limited data are available on Kp isolates outside the clinical setting, but Rodrigues et al (2022) highlighted that transmission can occur between clinical settings and MDR strains from foods. Moreover, Chiaverini et al (2022) reported the presence of one MDR strain from a wild boar in Italy.…”
Section: Introductionmentioning
confidence: 99%